Linking the processes of medication administration to medication errors in the elderly - Emerentia C. Nicholson; Anneleen Damons (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2022)
Background:Older people are more prone to chronic diseases than younger ones and typically receive multiple medications. Medication rounds in long-term care facilities (LTCFs) are usually lengthy, with most errors occurring during the administration phase. How nurses apply medication administration processes can affect resident outcomes. Aim: To determine the processes of medication administration followed by nurses in LTCFs as self-reported by them to identify possible factors associated with medication errors.